Comparison of MRI methods for measuring whole‐brain oxygen extraction fraction under different geometric conditions at 7T. Issue 3 (6th February 2022) - Lundberg, Anna; Lind, Emelie; Olsson, Hampus; Helms, Gunther; Knutsson, Linda; Wirestam, Ronnie
Abstract: Background and Purpose: Cerebral tissue oxygenation is a critical brain viability parameter, and the magnetic properties of hemoglobin offer the opportunity to noninvasively quantify oxygen extraction fraction (OEF) by magnetic resonance imaging (MRI). Ultrahigh‐field MRI shows advantages such as increased sensitivity to magnetic susceptibility differences and improved signal‐to‐noise ratio that can be translated into smaller voxel size, but also increased sensitivity to static and B1 field inhomogeneities. The aim was to produce a systematic comparison of three MRI‐based methods for estimation of OEF. Methods: OEF estimates in 16 healthy subjects were obtained at 7T utilizing susceptometry‐based oximetry (SBO), quantitative susceptibility mapping (QSM), and transverse relaxation rate (R2*). Two major draining veins, that is, the superior sagittal sinus (SSS) and the straight sinus (SS), were investigated, including mutual agreement between the methods in each of the two different vessels, agreement between vessels as well as potential vessel angle and vessel size dependences. Results: Very good correlation ( r = .88) was found between SBO‐based and QSM‐based OEF estimates in SSS. Only QSM showed a moderate correlation ( r = .61) between corresponding OEF estimates in SSS and SS. For SBO, a trend of increasing OEF estimates was observed as the SS vessel angle relative to the main magnetic field increased. No obvious size dependence could be established for any method. The R2*‐based OEF estimates were reasonable (35%‐36%), but the observed range was somewhat low. Conclusion: The results indicate that QSM is a promising candidate for assessment of OEF estimates, for example, providing reasonably robust estimates across a wide range of vessel orientations.